(untitled) (Journal of Oriental Studies, 2016)
In this article gathered inferences about linguacultural units and they are considered as a main object of science about linguacultural translation. Science about linguacultural translation is a new scientific direction, which unifies cultural studies, cultural linguistics and the science of translation. In this research work we have tried to give a new opinion to linguacultural units.